What predicts accounting prospective teachers' career choice? Evidence from the teaching internship program - Nurdian Susilowati; Amir Mahmud; Camelia Yunika Elisabet; Puji Novita Sari; Arif Santoso (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Prospective teachers should participate in pedagogical competency programs and engage in teaching practice to become professional teachers. The urgency of this study lies in examining the factors that influence career choices and assessing the quality of future professional teachers. This study investigates the effects of career self-efficacy (SE) and career interest (CI) on career choice (CC), with career exploration (CE) as a mediator, during the teaching internship. The population was 675 accounting education students who participated in the teaching internship program. The study used a simple random sampling method, yielding 251 respondents. The questionnaire included the career decision-making career self-efficacy scale-short form (CDMSE-SF), career exploration survey (CES), and career choice. A quantitative approach using structural equation modeling (SEM) was employed in WarpPLS 5.0. The study results show a direct relationship between career self-efficacy, career interest, and career exploration on career choice. Career exploration at the teaching internship also mediates the relationship between career self-efficacy and career interest in teaching career choice. It indicates that teaching internship programs increase students' confidence, thereby strengthening their resolve to pursue a career as an accounting teacher. Future studies may also explore other variables such as outcome expectations and personal background factors.